Fixed Point Theorems for Contractions of Rational Type with PPF Dependence in Banach Spaces - J. Rocha; B. Rzepka; K. Sadarangani (Journal of Function Spaces)
We prove the existence of the PPF dependent fixed point in the Razumikhin class for contractions of rational type in Banach spaces, by using a general class of pairs of functions. Our result has as particular cases a great number of interesting consequences which extend and generalize some results appearing in the literature.